Modulation of I‐wave generating pathways by theta‐burst stimulation: a model of plasticity induction. (12th November 2019) - Volz, Lukas J.; Hamada, Masashi; Michely, Jochen; Pool, Eva‐Maria; Nettekoven, Charlotte; Rothwell, John C.; Grefkes Hermann, Christian
Abstract : Key points: Mechanisms underlying plasticity induction by repetitive transcranial magnetic stimulation protocols such as intermittent theta‐burst stimulation (iTBS) remain poorly understood. Individual response to iTBS is associated with recruitment of late indirect wave (I‐wave) generating pathways that can be probed by the onset latency of transcranial magnetic stimulation applied to primary motor cortex (M1) at different coil orientations. We found an association between late I‐wave recruitment [reflected by anterior–posterior (AP)‐lateromedial (LM) latency; i.e. the excess latency of motor‐evoked potentials generated by transcranial magnetic stimulation with an AP orientation over the latency of motor‐evoked potentials evoked by direct activation of corticospinal axons using LM stimulation] and changes in cortical excitability following iTBS, confirming previous studies. AP‐LM latency significantly decreased following iTBS, and this decrease correlated with the iTBS‐induced increase in cortical excitability across subjects. Plasticity in the motor network may in part derive from a modulation of excitability and the recruitment of late I‐wave generating cortical pathways. Abstract: Plasticity‐induction following theta burst transcranial stimulation (TBS) varies considerably across subjects, and the underlying neurophysiological mechanisms remain poorly understood, representing a challenge for scientific and clinical applications. In human motor cortex (M1), recruitment of indirect waves (I‐waves) can be probed by the excess latency of motor‐evoked potentials elicited by transcranial magnetic stimulation with an anterior–posterior (AP) orientation over the latency of motor‐evoked potentials evoked by direct activation of corticospinal axons using lateromedial (LM) stimulation, referred to as the 'AP‐LM latency' difference. Importantly, AP‐LM latency has been shown to predict individual responses to TBS across subjects. We, therefore, hypothesized that the plastic changes in corticospinal excitability induced by TBS are the result, at least in part, of changes in excitability of these same I‐wave generating pathways. In 20 healthy subjects, we investigated whether intermittent TBS (iTBS) modulates I‐wave recruitment as reflected by changes in the AP‐LM latency. As expected, we found that AP‐LM latencies before iTBS were associated with iTBS‐induced excitability changes. A novel finding was that iTBS reduced AP‐LM latency, and that this reduction significantly correlated with changes in cortical excitability observed following iTBS: subjects with larger reductions in AP‐LM latencies featured larger increases in cortical excitability following iTBS. Our findings suggest that plasticity‐induction by iTBS may derive from the modulation of I‐wave generating pathways projecting onto M1, accounting for the predictive potential of I‐wave recruitment. The excitability of I‐wave generating pathways may serve a critical role in modulating motor cortical excitability and hence represent a promising target for novel repetitive transcranial magnetic stimulation protocols. Key points: Mechanisms underlying plasticity induction by repetitive transcranial magnetic stimulation protocols such as intermittent theta‐burst stimulation (iTBS) remain poorly understood. Individual response to iTBS is associated with recruitment of late indirect wave (I‐wave) generating pathways that can be probed by the onset latency of transcranial magnetic stimulation applied to primary motor cortex (M1) at different coil orientations. We found an association between late I‐wave recruitment [reflected by anterior–posterior (AP)‐lateromedial (LM) latency; i.e. the excess latency of motor‐evoked potentials generated by transcranial magnetic stimulation with an AP orientation over the latency of motor‐evoked potentials evoked by direct activation of corticospinal axons using LM stimulation] and changes in cortical excitability following iTBS, confirming previous studies. AP‐LM latency significantly decreased following iTBS, and this decrease correlated with the iTBS‐induced increase in cortical excitability across subjects. Plasticity in the motor network may in part derive from a modulation of excitability and the recruitment of late I‐wave generating cortical pathways.